(untitled) (Cybersecurity and Network Defense Research, 2024)
Cyber Threat Hunting (CTH) has emerged as a critical practice for organizations to proactively identify and mitigate cyber threats. This paper presents an in-depth analysis of the methods and tools used in CTH, focusing on the detection and neutralization of Advanced Persistent Threats (APTs) and insider threats. The paper begins by defining CTH and its importance in modern cybersecurity. It then explores various methods used in CTH, including signature-based detection, anomaly detection, and behavioral analysis. The paper also discusses the role of threat intelligence and machine learning in enhancing CTH capabilities. Additionally, the paper examines the tools and technologies commonly used in CTH, such as Security Information and Event Management (SIEM) systems, Endpoint Detection and Response (EDR) solutions, and Threat Intelligence Platforms (TIPs). The paper provides a comparative analysis of these tools, highlighting their strengths and limitations in the context of CTH. Overall, this paper aims to provide cybersecurity professionals and researchers with a comprehensive understanding of the methods and tools available for proactive cyber threat hunting, enabling them to better defend against APTs and insider threats.